MicroRNA profiling in BEAS-2B cells exposed to alpha radiation reveals potential biomarkers for malignant cellular transformation. Issue 6 (12th December 2020) - Dang, Xuhong; Lin, Haipeng; Li, Youchen; Guo, Xiuli; Yuan, Yayi; Zhang, Ruifeng; Li, Xiaozhen; Chai, Dongliang; Zuo, Yahui
Abstract: The carcinogenicity of radon has been convincingly documented through epidemiological studies of underground miners. The risk of lung cancer from radon exposure is due to the continuous radioactive decay of this gas and subsequent emission of high-energy alpha decay particles. And the bronchial epithelial cells are the main targets of radon exposure. However, there is a lack of early warning indicators of lung cancer caused by radon in the physical examination of populations involved in occupations with higher exposure to radon. To assess the potential of a molecular-based marker approach for the early detection of human lung cancer induced by radon, human bronchial epithelial cell injury models induced by alpha-particle irradiation were constructed. The results of transwell migration assay, transwell invasion assay, and the expression of the epithelial–mesenchymal transition-related proteins showed that malignant cell transformation could be triggered by alpha irradiation. Potential microRNAs (miRNAs) (hsa-miR-3907, hsa-miR-6732-3p, hsa-miR-4788, hsa-miR-5001-5p, and hsa-miR-4257) were screened using miRNA chips in cell models. The pathway analyses of miRNAs selected using DIANA-miRPath v3.0 showed that miRNAs involved in malignant cell transformation were associated with cell adhesion molecules, extracellular matrix receptor interaction, and proteoglycans in cancer, among others, which are closely related to the occurrence and development of carcinogenesis. Reverse Transcription Quantitative Real-Time PCR (RT-qPCR) assay showed that five screened miRNAs were up-regulated in five lung cancer tissue samples. In conclusion, the results indicated that hsa-miR-3907, hsa-miR-6732-3p, hsa-miR-4788, hsa-miR-5001-5p, and hsa-miR-4257 may be potential early markers of the malignant transformation of bronchial epithelial cells induced by alpha-particle irradiation.